Design, synthesis and biological evaluation of valepotriate derivatives as novel antitumor agents. Issue 51 (21st June 2017) - Zhang, Bo; Guo, Ruiying; Hu, Yongzhou; Dong, Xiaowu; Lin, Nengming; Dai, Xiaoyang; Wu, Honghai; Ma, Shenglin; Yang, Bo
Abstract : A series of valepotriate derivatives with novel skeleton were synthesized from commercial available genipin. Among them, 1e exhibited significant anti-proliferation activity against H1975 cells by inducing mitochondrion-mediated apoptosis. Abstract : Natural products remain the largest resources of lead compounds that can be used to develop novel anticancer drug candidates. Based on deacetylisovaltratum, a natural product with promising anticancer activity, herein we designed and synthesized of a series of valepotriate derivatives with a novel skeleton from commercially available genipin. In addition, a structure–activity relationship study demonstrated the importance of an epoxy group on the C1-position and the preferable size of the sidechain ((5-methylhexanoyl)oxy) on the C-7 position of valepotriates for their cytotoxic activities. The most potent compound1e showed moderate to good IC50 values against various cancer cells, ranging from 10.7 to 50.2 μM, which are comparable to that of deacetylisovaltratum. Additionally, we demonstrate that mitochondrion-mediated apoptosis would be its mechanism of action, thus enlightening the further development of novel valepotriate derivatives.